Reading in Multiple Orthographies: Differences and Similarities in Reading in Spanish and English for English Learners. Issue 3 (22nd July 2015) - Goodwin, Amanda P.; August, Diane; Calderon, Margarita
<x xml:space="preserve">Abstract</x> The current study unites multiple theories (i.e., the orthographic depth hypothesis and linguistic grain size theory, the simple view of reading, and the common underlying proficiency model) to explore differences in how 113 fourth‐grade Spanish‐speaking English learners (ELs) approached reading in their native language of Spanish, which is transparent, compared to their second language of English, which is more opaque. Contributions of different linguistic grain sizes (i.e., small grains assessed via phonological decoding and large grains assessed via morphological awareness), mediators (i.e., word reading, listening comprehension, and oral vocabulary), and transfer were explored. The results suggest that morphological awareness and phonological decoding contributed to reading comprehension in Spanish whereas only morphological awareness contributed to reading comprehension in English. For mediators, listening comprehension played a larger role than word reading in supporting reading comprehension in Spanish and English, but oral vocabulary only contributed in Spanish. No significant role of cross‐language transfer was found. Theoretical and educational implications are discussed.